Success factors in hospital network performance: evidence from Korea - Kim, Kwang-Jum; Burns, Lawton R (Health services management research : an official journal of the Association of University Programs in Health Administration, 2007)
Collaborative networks have become a common organizational strategy to deal with uncertain and dynamic environments. Like their counterparts in the USA, Korean hospitals are establishing cooperative relationships with one another, with varying performance results. This paper analyses some of the sources of variation in hospital network performance and identifies some of the possible success factors. The study finds that the quality of cooperation and information sharing between network partners are critical. The paper concludes with a discussion of the implications for researchers and practitioners.